Co2SnO4/CARBON PASTE ELECTRODE AS ELECTROCHEMICAL SENSOR FOR HYDROGEN PEROXIDE - Mosquera, Nerly; Aguirre, María J.; Ruiz-León, Domingo; García, Camilo; Arce, Roxana; Bollo, S. (Journal of the Chilean Chemical Society, 2017)
Hydrogen peroxide (H2O2) plays an important role as an intermediary in different biological, chemical and environmental systems. It has been widely used as an oxidizing and antimicrobial agent, in germicides production and textile and paper bleaching. However, it is well known, that H2O2 is a possible responsible in many diseases and is a chemical agent that threatens the environment, so it becomes important to detect peroxide with high accuracy. In this study, carbon paste electrode (CPE), modified with Co2SnO4 was synthesized and tested. It was successfully obtained a non-enzymatic H2O2 detection type sensor, based on Co2SnO4/ CPE composite, showing good linear response in concentration of H2O2 in the range of 88 – 605.9 μM.